Abuse of library materials in selected Nigerian special libraries - Fagbola Bolanle Oluyemisi; Ogunjobi Taiwo Elizabeth (African Journal of Behavioural and Scale Development Research, 2020)
An information Centre is an indispensable arm o/a viable research institute as it acquires and stocks previous intellectual endeavors. Timely access to collection is important as it has supported scholarship in the humanities, sciences and social sciences and remains the key to intellectual freedom. Mutilation and vandalism is a serious threat to the effective discharging of its responsibilities. This study used the descriptive research design with quantitative approaches to examine the extent to which library materials are vandalized in Nigerian research institutes' libraries. Schedule was used to elicit various forms of document abuses, collections vulnerable to theft, reasonsfor theft Result indicated Nigerian research institutes' libraries do experience tearing book pages (73.68 %.), borrowing books for friends/non staff(51.30 %.), deliberate mis-shelving q/' books (57.95 The study recommends regular orientation of staff and library users, provision of photocopier inside the library, regular stocktaking particularly of rare materials, digitalization of grey materials, training and retraining of security personnel posted to the library, and posting warning signs about the crime of vandalization of library materials.